Implementing Patient Family-Centered Care Grand Rounds Using Patient/Family Advisor Narratives - Fagan, Maureen B (J Patient Exp, 2015)
With the emerging trend of patient family–centered care in health care, it is essential that physicians be exposed to patient and family perspectives of care during medical education and training. Grand Rounds provides an ideal format for physicians to learn about patient family–centered care. At Brigham and Women’s Hospital, we sought to bring the voice of the patient to Patient Family–Centered Grand Rounds in order to expose clinicians to rich narratives describing the medical care received by patients/families and to ultimately change physician practice to reflect patient family–centered principles. We conducted a clinician survey and found promising results indicating that patient/family narratives can be effective at educating physicians about patient family–centered care.